Ministry of Education, 1961-1966. - Buganda Government
This includes correspondence addressed to the Minister of Education, the Permanent Secretary, Education Secretary General etc. It also incl udes speeches about the budgets of 1964-1966.
AR/BUG/1/3
Luganda and English
Shelf no. 1